Cyclin-dependent kinase 5 regulates degranulation in human eosinophils - Odemuyiwa, Solomon O (Immunology, 2015)
Degranulation from eosinophils in response to secretagogue stimulation is a regulated process that involves exocytosis of granule proteins through specific signalling pathways. One potential pathway is dependent on cyclin-dependent kinase 5 (Cdk5) and its effector molecules, p35 and p39, which play a central role in neuronal cell exocytosis by phosphorylating Munc18, a regulator of SNARE binding. Emerging evidence suggests a role for Cdk5 in exocytosis in immune cells, although its role in eosinophils is not known. We sought to examine the expression of Cdk5 and its activators in human eosinophils, and to assess the role of Cdk5 in eosinophil degranulation. We used freshly isolated human eosinophils and analysed the expression of Cdk5, p35, p39 and Munc18c by Western blot, RT-PCR, flow cytometry and immunoprecipitation. Cdk5 kinase activity was determined following eosinophil activation. Cdk5 inhibitors were used (roscovitine, AT7519 and small interfering RNA) to determine its role in eosinophil peroxidase (EPX) secretion. Cdk5 was expressed in association with Munc18c, p35 and p39, and phosphorylated following human eosinophil activation with eotaxin/CCL11, platelet-activating factor, and secretory IgA-Sepharose. Cdk5 inhibitors (roscovitine, AT7519) reduced EPX release when cells were stimulated by PMA or secretory IgA. In assays using small interfering RNA knock-down of Cdk5 expression in human eosinophils, we observed inhibition of EPX release. Our findings suggest that in activated eosinophils, Cdk5 is phosphorylated and binds to Munc18c, resulting in Munc18c release from syntaxin-4, allowing SNARE binding and vesicle fusion, with subsequent eosinophil degranulation. Our work identifies a novel role for Cdk5 in eosinophil mediator release by agonist-induced degranulation.